Advanced Endodermal Sinus Tumor With Contralateral Dermoid Tumor During Pregnancy: A Case Report and Literature Review - Chih-Wen Tseng; Chan-Chao Changchien (Elsevier, 2004)
Objective: An endodermal sinus tumor (EST) of the ovary and a contralateral dermoid cyst occur rarely in pregnancy. Alternative treatment for reducing the long-term sequelae in both the mother and fetus should be considered during pregnancy. Case Report: At 27 weeks of gestation, a patient was diagnosed with advanced EST, FIGO (International Federation of Gynecology and Obstetrics) stage IIIc, by magnetic resonance imaging and surgery. Following optimal debulking surgery, three cycles of multi-agent chemotherapy, consisting of 25 mg/m2 cisplatin and 100 mg/m2 etoposide on days 1 to 4, were instituted at 21-day intervals. Maternal serum !-fetoprotein and CA125 titers soon returned to normal pregnancy levels. A healthy male infant was delivered at 38 weeks of gestation by cesarean section, after which a second-look laparotomy was performed. The micropathologic findings were negative for malignancy, except that a dermoid tumor of the right ovary was confirmed. Consolidation treatment with two cycles of chemotherapy, consisting of 20 mg/m2 cisplatin and 100 mg/m2 etoposide on days 1 to 5 and a total of 30 mg/day of bleomycin on days 6 and 7, was administered at 28- day intervals. The patient had no evidence of disease for 16 months, and her infant son has shown adequate growth and normal development. Conclusion: For pregnant women with an EST of the ovary, the optimal treatment modalities might be initial optimal debulking surgery followed by alternative chemotherapy, and further standard chemotherapy after delivery.